2004
DOI: 10.1128/aac.48.2.396-403.2004
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Array-Generated Profiles of Cytokine Release from THP-1 Leukemic Monocytes Exposed to Different Amphotericin B Formulations

Abstract: Cytokine antibody arrays were used to establish the profiles of cytokine release from THP-1 monocytes exposed to different amphotericin B (AMB) drug delivery systems. Fungizone (FZ) and Amphotec (ABCD) caused the release of significantly more inflammatory molecules and the release of inflammatory molecules at higher levels than either AmBisome (L-AMB) or Abelcet (ABLC) after 6 h of treatment. Specifically, tumor necrosis factor alpha (TNF-␣), interleukin-8 (IL-8), GRO-(␣␤␥), monocyte chemoattractant protein-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…To the best of our knowledge, this is the first report of the effects of amphotericin B lipid formulations on gene expression of MIP-1␤. Previous observations on gene expression of MCP-1 in DAMB-treated MNCs or THP-1 cell lines (29) and on MIP-1␤ expression after THP-1 exposure to the four amphotericin B formulations (39) are consistent with our studies. Collectively these data suggest that DAMB and ABCD formulations may augment host response through MIP-1␤ release.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first report of the effects of amphotericin B lipid formulations on gene expression of MIP-1␤. Previous observations on gene expression of MCP-1 in DAMB-treated MNCs or THP-1 cell lines (29) and on MIP-1␤ expression after THP-1 exposure to the four amphotericin B formulations (39) are consistent with our studies. Collectively these data suggest that DAMB and ABCD formulations may augment host response through MIP-1␤ release.…”
Section: Discussionsupporting
confidence: 81%
“…Taking into consideration the adverse infusion-related reactions following DAMB administration, an imbalance in the protein synthesis of IL-1␤ and IL-1ra could indeed be responsible for the observed toxic adverse effects. DAMB-mediated up-regulation of IL-1␤ protein synthesis has previously been reported for THP-1 cells after incubation of DAMB at 5 g/ml for 2 and 6 h, respectively (26,39). However, stimulation of MNCs with 1 g of DAMB per ml for 24 h did not result in IL-1␤ synthesis (40) suggesting an optimum time window for IL-1␤ expression between 0.5 and 6 h. Keeping in mind the different conditions used, results from the present study and the previously mentioned reports are essentially in agreement with clinical data, where DAMB-induced IL-1␤ synthesis occurs between 2 and 6 h, which coincides with the time interval that adverse reactions are observed in humans (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data have predominantly been generated through in vitro exposure of monocytes to AmB (15). In addition, induction of cytokine release from THP-1 leukemic monocytes to different amphotericin B formulations has yielded similar results (23). Antibody array analysis in this previous study revealed that AmB has the greatest effect on TNF-␣ with no effect on IL-1 (23).…”
Section: Discussionmentioning
confidence: 58%
“…They determined the level of 25 plasma cytokines and were able to elucidate different cytokine profiles between patients with or without extraglandular manifestations [173]. Turtinen and coworkers studied the effects of different amphotericin B formulations on cytokine release from THP-1 leukemic monocytes and showed that TNF-alpha and IL-8 levels correlated well between the antibody microarray and quantitative ELISA measurements [174].…”
Section: Applicationsmentioning
confidence: 99%